Pemanfaatan Teknologi Internet of Things dalam Meningkatkan Hasil Pertanian Tanaman Melinjo - Sinaga, Anita Sindar; Nuraisana, Nuraisana; Panggabean, Erwin; Mulyani, Sri; Damayanti, Alfina (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2025)
Increasing productivity in the agricultural sector increasingly requires modernization of plant planting technology. This can be done by encouraging human resources such as helping farmers to be interested in knowledge about better and more appropriate agricultural techniques. Good agricultural technology must have a positive impact on the surrounding environment, not have a negative impact on human health and the surrounding environment, and be accessible and affordable to farmers. IoT tools are able to monitor soil through sensors that can measure soil conditions in real time. Sensors can observe various aspects of soil conditions, such as pH, humidity, temperature, and nutrients. IoT technology in the agricultural sector is utilized to achieve progress in melinjo plant production. Sensors as devices used can provide information on conditions such as soil humidity, air temperature, and humidity levels. Data obtained from sensors are sent via the internet to an intelligent system for analysis. The results of this analysis can provide information for farmers to make the right decisions to provide appropriate nutrition. Community service activities contribute to increasing melinjo plant agricultural yields in Dalu Sepuluh Village through the use of IoT technology for automatic plant watering.